IMPLICATIONS OF CONSTITUTIONAL COURT DECISION NUMBER 003/PUU-IV/2006 ON THE APPLICATION OF UNLAWFUL ELEMENTS IN ARTICLE 2 OF THE CORRUPTION ERADICATION LAW - Febri Fitra Kusuma; I Nyoman Nurjaya; Yuliati (CV. RADJA PUBLIKA, 2024)
One of the elements found in Article 2 of the Corruption Law is the element of illegality. In the explanation of Article 2, it is stated that